One swallow doesn't make a summer: New evidence on anchoring effects - Zacharias Maniadis; Fabio Tufano; John A. List (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2013)
Some researchers have argued that anchoring in economic valuations casts doubt on the assumption of consistent and stable preferences. We present new evidence that questions the robustness of certain anchoring results. We then present a theoretical framework that provides insights into why we should be cautious of initial empirical findings in general. The model importantly highlights that the rate of false positives depends not only on the observed significance level, but also on statistical power, research priors, and the number of scholars exploring the question. Importantly, a few independent replications dramatically increase the chances that a given original finding is true.
Keywords: 330